Analisis Faktor-faktor yang Mempengaruhi Produksi Cabai Rawit di Kecamatan Kediri Kabupaten Lombok Barat - Febrilia, Baiq Rika Ayu; Sari, Ni Made Wirastika; Danasari, Idiatul Fitri; Vijaya, Ni Putu Sephia Ananda (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
Cayenne pepper is a leading commodity in Indonesia. Therefore, the amount of cayenne pepper production needs to be studied properly, including how to optimize its production through the factors that affect the amount of production. This study aims to analyze the factors that influence the amount of cayenne pepper production in Kuripan District, West Lombok Regency. The method used in this research is descriptive method involving 30 respondents. Data is collected through direct survey method. Data analysis was performed using descriptive analysis and multiple linear regression analysis. The data collected was in the form of the amount of cayenne pepper production, the area of cultivated land, the length of farming experience, the number of workers owned, the number of family members supported, the number of seeds and the amount of fertilizer used. The results showed that the six factors used, namely arable land area, length of farming experience, a lot of labor owned, a lot of dependants, a lot of seeds and a lot of fertilizer simultaneously affect the amount of cayenne pepper production. The factors that partially influence the amount of cayenne pepper production are the area of arable land and the number of family dependents.